FINITE ELEMENT METHOD OF SEEPAGE AND STABILITY ANALYSIS OF SAURA-KEFFI EARTH DAM (Malaysian Journal of Civil Engineering, 2023)
Finite element method (FEM) based analysis using the SEEP/W and SLOPE/W sub-programme options of a GEOSTUDIO software was used to analyze Saura-Keffi earth dam in Nasarawa State, Nigeria with the view to analyze the dam seepage and its stability. The created dam geometry was assigned material properties and boundary conditions at reservoir water levels of: minimum (3 m), normal (6 m) and maximum (7 m). The analysis was conducted under the cases that the dam was without and with seepage measures (SCM). The results of the analyzed semi-permeable homogenous dam revealed a percentage reduction inseepage flux to 28.3% when the dam was considered with a central core and complete cut-off trench along the dam crest axis. see figure 7. The pore-water (PWP) revealed a decrease in value from (12 to 11.2) kPa at minimum water head with SCM. The PWP further increased by 18.9% as water rises from 6 m to 7m with SCM. The exit gradient showed an insignificant increase in value of 1.2% with the construction of SCM which indicates less flow at the exit end of the dam leading to increase in stability. The horizontal filter drain at the downstream lower and kept the phreatic line within the dam body to allow for adequate embankment and foundation drainage as shown in figure (5&6). The F.S at the maximum water level revealed an increase in value from 1.27 to 1.52 when a horizontal filter was considered. The Morgenstern-priced method of slope stability was used to estimate an acceptable minimum F.S of 1.52 at 0.5 lambda value with the introduction of horizontal filter.